STUDYING THE RELATIONSHIP MODEL BETWEEN ENTREPRENEURSHIP INSIGHT AND BUSINESS PERFORMANCE: A STUDY OF MSMEs IN INDONESIA - Setyawati, Amelia; Sugangga, Amelia; Yudhyani, Eka; Febrina, Reni (SULTANIST: Jurnal Manajemen dan Keuangan, 2024)
This research aims to examine the relationship model between entrepreneurial orientation (EO), entrepreneurship insight (EI), information technology adoption (ITA), and business performance (BP) in MSMEs in Indonesia. The research method used is a quantitative approach with survey techniques of MSME actors in various sectors in Indonesia. Data was collected through a questionnaire adapted from previous research. The research sample consisted of 200 respondents selected using a purposive sampling technique, with the criteria being that the business had been running for at least two years and had access to information technology. The results of the research data analysis conclude that entrepreneurial orientation (EO), entrepreneurship insight (EI), and information technology adoption (ITA) have a positive and significant effect on business performance (BP). The research results will provide deeper insight into the influence of EO, EI, and ITA on the business performance of MSMEs in Indonesia. It is hoped that this research can also provide recommendations for MSME actors and policymakers to increase the competitiveness of small businesses through implementing entrepreneurial strategies and adopting technology. Thus, this research contributes to the development of MSME business theory and practice in the digital era and supports efforts to improve the performance of MSMEs in Indonesia.